2008
DOI: 10.1017/s0022215108001916
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of adenoidal obstruction in children: clinical symptoms compared with roentgenographic assessment

Abstract: Clinical rating of adenoidal symptoms in children provides a reasonably reliable assessment of the presence and severity of nasopharyngeal airway obstruction. This technique of assessment is easy to use and is particularly valid when obstruction is either minimal or gross.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 19 publications
4
41
0
Order By: Relevance
“…The SS clinical parameter utilized in our study was validated previously against radiologic assessment and was shown to reliably evaluate the degree of airway obstruction in children with obstructive adenoid vegetations [14]- [16]. It is an easy-to-use tool to assess the impact of airway obstruction on sleep disturbance, physical suffering, and daytime problems of the children as perceived by the caregivers, before and after AT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The SS clinical parameter utilized in our study was validated previously against radiologic assessment and was shown to reliably evaluate the degree of airway obstruction in children with obstructive adenoid vegetations [14]- [16]. It is an easy-to-use tool to assess the impact of airway obstruction on sleep disturbance, physical suffering, and daytime problems of the children as perceived by the caregivers, before and after AT.…”
Section: Discussionmentioning
confidence: 99%
“…'The symptomatology scores' [14] were generated using set of questions designed to grade the severity of the most typical symptoms of adenotonsillar hypertrophy that indicated breathing and sleep disturbances. The following numeric values were assigned to snoring and mouth breathing: 0-absent, 1-occasionally during sleep, 2-regularly during sleep, 3-regularly during sleep and daytime.…”
Section: Study Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…All our children were free of acute infections like acute tonsillitis, adenoiditis and rhinosinusitis. In a study by FT Orji et al 19 , there was significant correlation between AN ratio and age where younger children were observed to have more severe symptoms. Our study also showed maximum number of B type tympanograms in the age group 4-6 years with mean AN ratio of 0.73 showing significant correlation ( P<0.001).…”
Section: Discussionmentioning
confidence: 91%